Chinese Indonesians’ Thoughts About Indonesia’s Government Handling the 1998 Tragedy - Nikita Christy Ignesius (Institute of Research and Community Outreach - Petra Christian University, 2022)
Two decades passed by but the 1998 riot case is still remembered as a traumatic event for Chinese Indonesian people. Started from the economy crisis in July 1997 where Rupiah currency dropped and gave a huge damage to the Indonesia economy and politic section. This crisis made the poor non Chinese Indonesian envied the Chinese Indonesians. The riot reached its peak in May 1998 where Chinese Indonesians got harassed. Many Chinese Indonesians decided to leave Indonesia to live in other countries temporary or forever. Each generation keep reminding this incident made the young Chinese Indonesian generation aware of the Non Chinese Indonesian. This research aims to reveal the thoughts of Chinese Indonesian about the Indonesian government in handling the 1998 riot and examine the reason behind the Chinese Indonesian thoughts. The researcher also hoped that this research can be used as reference in other research related to this 1998 riot.Keywords : 1998 riot, Chinese Indonesians, Indonesia’s Government